Genome-wide meta-analysis of insomnia prioritizes genes associated with metabolic and psychiatric pathways - Watanabe, Kyoko; Jansen, Philip R.; Savage, Jeanne E.; Nandakumar, Priyanka; Wang, Xin; Hinds, David A.; Gelernter, Joel; Levey, Daniel F.; Polimanti, Renato; Stein, Murray B.; Van Someren, Eus J. W.; Smit, August B.; et al. (Nature genetics, 2022)
Insomnia is a heritable, highly prevalent sleep disorder for which no sufficient treatment currently exists. Previous genome-wide association studies with up to 1.3 million subjects identified over 200 associated loci. This extreme polygenicity suggested that many more loci remain to be discovered. The current study almost doubled the sample size to 593,724 cases and 1,771,286 controls, thereby increasing statistical power, and identified 554 risk loci (including 364 novel loci). To capitalize on this large number of loci, we propose a novel strategy to prioritize genes using external biological resources and functional interactions between genes across risk loci. Of all 3,898 genes naively implicated from the risk loci, we prioritize 289 and find brain-tissue expression specificity and enrichment in specific gene sets of synaptic signaling functions and neuronal differentiation. We show that this novel gene prioritization strategy yields specific hypotheses on underlying mechanisms of insomnia that would have been missed by traditional approaches. Genome-wide association meta-analysis of insomnia in 593,724 cases and 1,771,286 controls identifies 554 risk loci and implicates specific biological pathways through gene prioritization.